THE PODCAST IN YOUTH AND ADULT EDUCATION - Sobrinho, Benedito Braz; Sobrinho, Benedito Braz; Fontenele, Flavia Azevedo Albuquerque; de Vasconcelos, Francisca Antonia Araujo; Braz, Francisca de Fátima Lemos; Coutinho, Manoel Flávio; da Silva, Maria de Lourdes Rocha; de Melo, Maria José Coutinho; Ribeiro, Mayra Aparecida Mendes; da Silva, Raimunda Maria; Brasil, Thamylles França Moita (Seven Editora, 2025)
The presence of technology in the classroom has become a reality, with it finding a multitude of possibilities that help teachers in their pedagogical work. Thus, this work addresses one of the most common and easily produced media resources, the result of technological advances today, the podcast. Due to its popularity, this resource gains space in this work, whose main objective is to understand its importance and applicability in the educational environment. To this end, we sought to develop bibliographical research that could unveil the origin and results of the use of this tool in schools, in addition to developing a proposal for using the podcast in a youth and adult education school, therefore requiring a brief on-site research at the school in question in order to verify the real possibility of implementing the tool in the routine of the institution visited. Finally, it can be understood that the characteristics of the use of digital tools in education is increasingly a reality that cannot be ignored by educators, but improved for appropriate use according to each educational reality.DOI: https://doi.org/10.56238/sevened2025.038-059